Indonesia's Electronic Export Potential in The Global Market with Gravity Panel Model Approach - Kurniawati, Renny; Nawiyah, Nawiyah; Sutjiatmo, Bayu Prabowo (Westscience Press, 2023)
The purpose of this study is to calculate Indonesia's electronic export potential to 14 countries during the period 2007-2022 using a panel-gravity approach using the PPML technique. The results of this study confirm the positive and significant relationship between Indonesia's electronics exports and the main component of the gravity model, namely Indonesia's GDP and trading partners. Another variability is the economic openness of trading partners has a positive relationship and exchange rates have a positive but not significant relationship. Variability of distance, and trade agreements have a negative relationship with Indonesia's electronic exports. The results for electronic export potential show that Indonesian electronics still have a lot of leverage to increase its exports to 9 countries. Thus, the position of the electronics industry as a potential industry can be carried out by targeting these countries. But to capitalize on the potential benefits of electronics exports, policymakers need to strengthen infrastructure and regulations related to the electronics industry.